A taxonomic monograph of Myrcia sect. Sympodiomyrcia (Myrteae, Myrtaceae) - Santos, Matheus F.; Lucas, Eve; Sano, Paulo T. (Phytotaxa, 2018)
Myrcia contains nearly 800 species and is divided into nine sections, one of them, Myrcia sect. Sympodiomyrcia, has recently been recognized and formally described. This study presents a taxonomic monograph of the group and revises its literature and taxonomic history. Myrcia sect. Sympodiomyrcia is mainly characterized by the presence of cataphylls at the base of internodes, sympodial branching at the base of inflorescences and free and deciduous calyx lobes. Myrcia sect. Sympodiomyrcia is distributed between the Guiana Shield and the central-eastern portion of Brazil (Atlantic Forest and Cerrado Domains). Morphological characterization of organs and structures is provided, as well as distribution statements, morphological differences with other sections of Myrcia and an identification key. A full taxonomic treatment as well as conservation status and images of representative specimens of each species are provided. Twenty one species are here accepted in Myrcia sect. Sympodiomyrcia: Myrcia ascendens, M. attenuata, M. bicarinata, M. bicolor, M. cataphyllata, M. costeira, M. densa, M. foveolata, M. insigniflora, M. lenheirensis, M. mucugensis, M. mutabilis, M. nitida, M. plusiantha, M. rupestris, M. subavenia, M. subcordata, M. subterminalis, M. summa, M. tenuifolia and M. truncata.